Influence of artificial food provisioning from fisheries on killer whale reproductive output. (25th September 2014) - Tixier, P.; Authier, M.; Gasco, N.; Guinet, C.
Abstract Prey availability is a critical factor influencing demographic trajectories of long‐lived, top predators, which may therefore be strongly affected by artificial food provisioning. In the Crozet archipelago, killer whales feed on a wide range of species including birds, marine mammals and fish. Following the development of the Patagonian toothfish fisheries in 1996, killer whales began to also depredate longlines. Social groups, hereafter referred to as matrilines, exhibited different levels of interaction; some were involved in most of the depredation events, while others were never observed interacting with fisheries. These differences in interaction levels influenced reproduction. An extensive photo‐identification effort from 2003 to 2012 allowed us to estimate the probability of calving for 21 reproductive females. Using multi‐model inference, we found a positive effect of depredation on female calving rate. These results suggest an effect of artificial food provisioning on female reproductive output with potentially far‐reaching consequences on the demography of the Crozet killer whale population. Our findings evidence the need to account for both intra‐population heterogeneity and level of interaction with fisheries when assessing conservation strategies of long‐lived marine predators involved in similar depredation worldwide.